(untitled) (Islas, 2021)
The notion of economic development and its evolution has been approached by schools of economic thought, and from all ideological currents. Cuba has not been the exception; it has been actively present in all stages of the national history. Carlos Rafael Rodríguez is a reference point for the Marxist approach of the aforementioned topic. His active bibliography is studied from historical materialism, in addition, the logical-abstract and analysis-synthesis methods, as well as triangulation are applied. We analyze his work, without encomiums; exposing his contributions to the process of evolution of the notion of economic development in Cuba, and recognizing the validity of his legacy, 108 years after his birth.